Association between Triple-Negative Breast Cancer and Socioeconomic and Cultural Factors in Southeast Anatolia: A Single-Center Experience - ALKIŞ, HİLAL (My University, 2022)
Amaç: Triple negatif meme kanseri (TNMK) genç yaş, tanı anında ileri evre hastalık, etnik köken, düşük sosyoekonomik statü (SES) ve kötü prognozla ilişkilidir. Bu çalışmanın amacı Güneydoğu Anadolu’da yaşayan triple negatif meme kanserli hastaların klinikopatolojik özelliklerinin yanı sıra TNMK ile sosyoekonomik ve kültürel faktörler arasındaki ilişkiyi araştırmaktır. Gereç ve Yöntem: Toplam 875 hasta çalışmaya dâhil edildi. Hastaların tanı anındaki yaşı, klinikopatolojik özellikleri, yaşadıkları bölge (kırsal veya kentsel), SES ve etnik kökenleri (Arap, Ermeni, Kürt, Türk) kaydedildi. Hastaların SES’i, eğitim düzeyi, aylık gelirleri ve sağlık güvencesi durumuna göre düşük ve yüksek olmak üzere ikiye ayrıldı. Düşük SES grubuna okur-yazar olmayan, sağlık sigortası ve düzenli aylık geliri olmayan hastalar alındı. TNMK’li hastaların klinikopatolojik özellikleri üzerine SES’in etkisini analiz için Ki-kare testi kullanıldı. LogRank testi kullanılarak sağ kalım analizi yapıldı. Bulgular: Hastaların %10’unda (n=87) TNMK tanısı mevcuttu. Medyan tanı yaşı TNMK olan hastalarında 44 (24-84) ve TNMK olmayan hastalarında ise 47 (20-85) olarak bulundu. TNMK oranları 40 yaş ve altındaki hastalarda daha fazlaydı. Genç yaş, düşük SES ve Arap ile Kürt etnik kökenlilerde TNMK oranları daha yüksek bulundu (P < 0,04). Sonuç: Güneydoğu Anadolu bölgesindeki hastaların çoğunluğu premenopozal olmasına rağmen TNMK oranları batılı ülkelerdeki oranlardan daha düşük bulunmuştur. Sosyoekonomik ve kültürel faktörler TNMK olan hastalarda tümör biyolojisini etkileyebilmektedir. Genç yaş, düşük SES ve etnik kökenin daha yüksek TNMK oranları ve daha kötü prognozla ilişkili olduğu bulunmuştur

Objective: Triple-negative breast cancer (TNBC) is associated with younger age, advanced stage at diagnosis, ethnicity, lower socioeconomic status (SES), and poor prognosis. The aim of the study was to investigate clinicopathologic features of TNBC patients living in Southeast Anatolia, and the association between socioeconomic and cultural factors and TNBC. Material and Method: A total of 875 women were included in the study. Patients’ age at diagnosis, living area (rural or urban), SES, ethnicity (Arabic, Armenian, Kurdish, and Turkish) and clinicopathologic features were recorded. SES of the patients was categorized as lower and higher according to educational and health insurance status, and household income. Patients who were illiterate and did not have a health insurance and regular monthly household income were grouped as lower SES. Effects of SES on clinicopathologic features of the patients with TNBC were analyzed using qhi-square test. The difference in survival across strata was compared with the Log-Rank test. Results: Ten percent of the patients (n=87) were diagnosed with TNBC. Median age at diagnosis for patients with TNBC and nonTNBC was 44 years (24-84) and 47 years (20-85), respectively. TNBC rates were higher in patients ≤ 40 years. Younger age, lower SES, and Arabic and Kurdish ethnicities were associated with higher rates of TNBC (P < 0.04). Conclusion: Although the majority of the breast cancer patients living in Southeast Anatolia were premenopausal, the rate of TNBC among them was found lower than the general rate of western countries. Socioeconomic and cultural factors may affect tumor biology and prognosis of the disease in patients with TNBC. In our study, younger age, lower SES, and ethnicity were associated with higher rates of TNBC and worse prognosis.
Güneydoğu Anadolu’da Triple Negatif Meme Kanseri ile Sosyoekonomik ve Kültürel Faktörler Arasındaki İlişki: Tek Merkez Deneyimi
Keywords: Sağlık Bilimleri; Health Sciences; Klinik Tıp (MED); Clinical Medicine (MED); Triple-negative breast cancer; socioeconomic factors; prognosis